Integration of supply chain management and marketing management: A case study on FMCG products under Nestle Bangladesh - Samdani, Syed Zarif (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.